Extraction of a Large Central Airway Foreign Body Using Flexible Bronchoscopy Combined with an Endobronchial Blocker. (4th May 2016) - Paradis, Tyler; Wollenberg, Michael; Tieu, Brandon
Abstract : Adult foreign body (FB) aspiration is an uncommon but potentially fatal event. Options for extraction include flexible bronchoscopy (FLXB), rigid bronchoscopy (RB), and surgical extraction. We report the case of a large, smooth aspirated rock causing airway obstruction in an elderly male. RB is generally the preferred approach for extraction of a large complex FB; however, due to its size, the FB had to be removed using FLXB combined with an endobronchial blocker. In this report, we describe the anesthetic and surgical considerations and the novel technique used to extract the FB.